Management of Pica associated with relational stress in an adult woman: A case report - Prerna Sharma,; Ananya Mahapatra,; Aanchal Narang, (Indian Journal of Case Reports, 2021)
Pica is a feeding and eating disorder where there is the consumption of non-nutritive substances not consistent with cultural practices or social norms. Its etiology is still unknown, and its presence seems to vary with patients’ characteristics and the specific behaviors involved. Here, we are reporting a late-onset case of a 23-year-old female, presenting with consumption of wall scrapings, with some underlying early maladaptive schemas, and psychosocial triggers leading to eating scrapings off the walls.